OCCURRENCE OF PUERULUS OF SPINY LOBSTER PANULIRUS POLYPHAGUS (HERBST) ALONG THE MADRAS COAST - Girijavallabhan, K G; Devarajan, K (Indian Journal of Fisheries, 2011)
The occurrence of the pusrulus stagi of the spiny lobster, Panulinis polyphagus (Herbst) is reported for the first time from the Madras coast along with brief notes on the material.